Evaluating the diagnostic validity of the cerebellar cognitive affective syndrome (CCAS) in pediatric posterior fossa tumor patients. Issue 1 (12th May 2022) - Hoffmann-Lamplmair, Doris; Leiss, Ulrike; Peyrl, Andreas; Slavc, Irene; Czech, Thomas; Gram, Alexandra; Pletschko, Thomas
Abstract: Background: The aim of this case-control study was to investigate the severity of the cerebellar cognitive affective syndrome (CCAS) in patients treated for pediatric posterior fossa tumors (PFT) and evaluate its diagnostic validity and predictive value for long-term effects. Methods: Using neuropsychological test data from 56 patients with PFT (average age: 14 years), the severity of deficits in the CCAS core areas (executive functions, verbal functions, visuospatial abilities and emotions/behaviour) was examined. Neuropsychological and academic long-term outcomes of patients with CCAS were compared to two control groups of PFT patients (treated with either surgery or surgery followed by radio-/chemotherapy) without the syndrome. Risk factors associated with various deficits were considered. Results: All but one PFT patient suffered from slight to severe impairments in at least one CCAS domain, while complete CCAS occurred in 35.7%. Seven years after tumor diagnosis CCAS patients performed worse in information processing, logical reasoning, verbal functions, visuospatial skills, and executive functioning and required more special educational support compared to the control groups. CCAS patients performed equally poor as patients treated with chemo-/radiotherapy in tasks measuring information processing speed. Risk factors were significantly associated with deficits in information processing speed but not CCAS emergence. Conclusions: Deficits in the core CCAS domains are commonly found in PFT patients, but varying in severity, which suggests the syndrome to be continuous rather than dichotomous. However, the validity of CCAS diagnosis was low and unspecific. The exclusion of relevant functions typically impaired in PFT patients (eg, information processing) resulted in difficulties being overlooked.